Analisis Hukum terhadap Penolakan Perdamaian oleh Kreditur yang Diajukan Debitur pada Penundaan Kewajiban Pembayaran Utang - Dahlan, Muhammad Fitratallah; Deviany, Oky; Aswan, Muhammad (Fakultas Syariah INSURI Ponorogo, 2023)
This research evaluates the peace arrangements in PKPU and their potential to cause injustice to debtors. It also examines the legal implications of bankruptcy decisions on rejected peace plans submitted by debtors to PKPU. The research uses a statutory, conceptual, and case approach, drawing from primary legal materials such the 1945 Constitution of the Republic of Indonesia, BW, HIR, RBG, the Bankruptcy and PKPU Laws, the Judicial Powers Law as well as PKPU decisions. Secondary sources such as scholarly articles and books authored by bankruptcy and PKPU experts, as well as tertiary sources such as dictionaries and encyclopedias, were also utilized. The research findings reveal that: (1) the rejection of the settlement by the creditor causes injustice, due to the creditor's unreasonable grounds for rejection. However, the Bankruptcy Law and PKPU grant rights to the creditor under Article 222 paragraph (2), Article 289, and Article 281, enabling them to bankrupt the debtor on the grounds that the debtor's peace plan does not cover the entire amount of the debt. (3) a bankruptcy decision resulting from the rejection of a debtor's peace plan is an unsuitable decision that causes significant losses for both the debtor and the creditor.